2018
DOI: 10.1002/aoc.4414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Ni (II) complexes supported by phenoxy/naphthoxy‐imine ligands with pendant N‐ and O‐donor groups and their use in ethylene oligomerization

Abstract: A series of new Ni(II) complexes of general formula Ni{ZNO} Br (2a‐i) (ZNO = phenoxy/naphthoxy‐imine with pendant N‐ and O‐donor groups) were prepared and characterized by elemental analysis, IR spectroscopy, ESI‐HRMS, and by X‐ray crystallography for 2e. In the solid state, 2e features a monomeric structure with κ3 coordination of the monoanionic naphthoxy‐imine‐quinoline ligand onto the nickel center. Upon activation with MAO, both classes of nickel catalysts were able to produce selectively 1‐butene (81.5–9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…One of the strategies employed with monoanionic tridentate ligands is to introduce an additional donor group into bidentate monoanionic ligands known to possess interesting properties as regards the oligomerization of ethylene. 140 Wang et al 141 reported tridentate phenoxy-imine based nickel complexes 53 (Figure 29). The complex 53 transforms ethylene into butenes as the main product in the presence of MAO.…”
Section: Tridentate Monoanionic Ligands Llxmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the strategies employed with monoanionic tridentate ligands is to introduce an additional donor group into bidentate monoanionic ligands known to possess interesting properties as regards the oligomerization of ethylene. 140 Wang et al 141 reported tridentate phenoxy-imine based nickel complexes 53 (Figure 29). The complex 53 transforms ethylene into butenes as the main product in the presence of MAO.…”
Section: Tridentate Monoanionic Ligands Llxmentioning
confidence: 99%
“…In presence of ethylene, the nickel(II) complexes 54 activated by AlEtCl 2 predominantly produce butenes and hexenes as the main products with good activity (Table 6). Casagrande et al 140 studied the impact of replacing the phenoxy moiety with a naphthoxy moiety in a phenoxy-imine based nickel catalyst bearing a pendant oxygen group on the oligomerization of ethylene 55a−b (Figure 29). All complexes are active in the oligomerization of ethylene when activated by MAO.…”
Section: Tridentate Monoanionic Ligands Llxmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the temperature from 10°C to 0°C leads to similar activity [TOF = 19.9 × 10 3 (mol ethylene) (mol Ni) −1 h −1 ] and selectivity (95.2%) for 1-butene. [37] On the basis of these preliminary results, MAO was selected to investigate the effect of the [Al/Ni] molar ratio on the TOF and selectivity for the production of 1-butene. However, despite the low activity at 20°C and 30°C, Ni1 still operates with good selectivity for 1-butene production (94.6 and 91.9%).…”
Section: Ethylene Oligomerization Studiesmentioning
confidence: 99%
“…These findings are in line with ours previously reported studies involving nickel catalytic systems. [52,53] Thus, considering the high activity and selectivity for 1-butene production, MAO was chosen for the optimization process varying some oligomerization parameters such as temperature, lifetime, and the amount of cocatalyst.…”
Section: Ethylene Oligomerizationmentioning
confidence: 99%